Associations Between Comorbidities and Severe Maternal Morbidity. Issue 2 (24th June 2021) - Brown, C.C.; Adams, C.E.; George, K.E.; Moore, J.E.
Abstract : ( Obstet Gynecol . 2020;136:892–901) Severe maternal morbidity (SMM) includes long- or short-term consequences to a woman's health due to pregnancy and childbirth. Since 1993, the US has seen a two-fold increase in the rate of SMM. The rate of SMM is nearly double for non-Hispanic Black women compared to non-Hispanic white women. Compared to women without chronic conditions, women with multiple chronic conditions are 3.8 times more likely to experience severe maternal morbidity and mortality. This study investigated the differences in risk of SSM associated with having zero, one, two or three or more comorbidities. The hypothesis of the study was that a higher number of comorbidities would be associated with a greater risk of SMM, and that these associations would vary by race.